TrkA serves as a virulence modulator in Porphyromonas gingivalis by maintaining heme acquisition and pathogenesis - Zou, Renjie; Zhao, Lei; Shen, Daonan; Wu, Yafei (Frontiers in Cellular and Infection Microbiology, 2022)
Periodontitis is an inflammatory disease of the supporting tissues of the teeth, with polymicrobial infection serving as the major pathogenic factor. As a periodontitis-related keystone pathogen, Porphyromonas gingivalis can orchestrate polymicrobial biofilm skewing into dysbiosis. Some metatranscriptomic studies have suggested that modulation of potassium ion uptake might serve as a signal enhancing microbiota nososymbiocity and periodontitis progression. Although the relationship between potassium transport and virulence has been elucidated in some bacteria, less is mentioned about the periodontitis-related pathogen. Herein, we centered on the virulence modulation potential of TrkA, the potassium uptake regulatory protein of P. gingivalis, and uncovered TrkA as the modulator in the heme acquisition process and in maintaining optimal pathogenicity in an experimental murine model of periodontitis. Hemagglutination and hemolytic activities were attenuated in the case of trkA gene loss, and the entire transcriptomic profiling revealed that the trkA gene can control the expression of genes in relation to electron transport chain activity and translation, as well as some transcriptional factors, including cdhR, the regulator of the heme uptake system hmuYR. Collectively, these results link the heme acquisition process to the potassium transporter, providing new insights into the role of potassium ion in P. gingivalis pathogenesis.